Liver adenomatosis mimics metastatic liver involvement on FDG-PET/ CT - Bělohlávek, O; Jarůšková, M; Šmakal, M (Klinicka onkologie, 2023)
BACKGROUND: Liver adenomatosis is a very rare disease. In the literature, we were able to find only two case reports documenting the appearance of this disease on PET/CT with 18F-fludeoxyglucose (FDG-PET/CT). CASE: Numerous liver foci were detected during sonography in a 52-year-old female patient with uncharacteristic pain in the epigastrium without oncological history, with negative oncomarkers and without clinical signs of generalized neoplasia. Complementary MRI examination expressed the suspicion of metastatic origin of the foci, and FDG-PET/CT was indicated in order to identify the primary tumour and assess the extent of the disease. A whole-body FDG-PET/CT examination showed multiple (> 20) markedly hypermetabolic liver foci with 3-20 mm in diameter, reaching a relative accumulation of SUVBWmax = 13, together with several ametabolic cysts; elsewhere in the scope of the examination, focally pathologically increased metabolic activity was not evident. Subsequently, the patient underwent a biopsy targeted at one of the hypermetabolic liver foci with the finding of HNF 1A inactivated variant of hepatocellular adenoma; primary or secondary malignancy was not demonstrated. Considering the histological findings and the large number of liver foci, the final diagnosis of liver adenomatosis was set. The patient remains under continuous observation. CONCLUSION: Adenomatous foci were markedly hypermetabolic during FDG-PET/CT examination and could not be distinguished from tumour metastases by this method. Our finding is consistent with two other observations we were able to find in the literature.
Keywords: Positron Emission Tomography Computed Tomography; počítačová rentgenová tomografie; Neoplasms; hepatocellular adenoma; Radiopharmaceuticals; Positron-Emission Tomography; pozitronová emisní tomografie; adenomatosis; Tomography, X-Ray Computed; fluorodeoxyglukosa F18; radiofarmaka; lidé; ženské pohlaví; játra; Fluorodeoxyglucose F18; Humans; FDG-PET/CT; PET/CT; nádory; Liver; Female; liver; lidé středního věku; Middle Aged